CHARACTERISTIC OF RAINFALL PATTERN BEFORE FLOOD OCCUR IN INDONESIA BASED ON RAINFALL DATA FROM GSMaP - ARYASTANA, PUTU; Tanaka, Tasuku; Mahendra, M.S. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 2 (2012), 2015)
Floods are natural disasters that took place almost all over the world including Indonesia. Indonesia is very vulnerable to disasters because has characteristic a huge amount of rainfall throughout the year. Flood disaster is one of the disasters that often occur in Indonesia. GSMaP is one kind product of satellite precipitation has one hour temporal resolution, 0.1x0.1 degree horizontal resolution, world-wide coverage and operated by JAXA. In this study were investigate the characteristic of rainfall pattern before floods occur by processing hourly GSMaP MVK at each location large flood events occur in Indonesia on 2006-2010. The large flood events data collected from Dartmouth Flood Observatory (2006-2010) and Ministry of Public Works of the Republic of Indonesia (2006-2010). Based on the processing result, generally Indonesia has two characteristic of rainfall patterns before floods occur namely: short term rainfall period and long term rainfall period. Based on the compilation and classification of 69 locations large flood events in Indonesia, from three rainfall pattern before flood occur it obtained 42 locations or 60.87% in the category short term rainfall period, 27 locations or 39.13% in the category long term rainfall period.
Keywords: flood, rainfall pattern, GSMaP